2018
DOI: 10.3892/mmr.2018.8682
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-383 suppresses cell proliferation and invasion in colorectal cancer by directly targeting paired box 6

Abstract: Colorectal cancer (CRC) is the third-most prevalent cancer and the fourth‑most common cause of cancer-associated fatality worldwide. The expression and biological roles of microRNAs (miRNAs/miRs) in tumourigenesis, and their regulatory function in a number of biological processes correlated with cancer have been investigated. miR‑383 has been reported to be deregulated in several human cancer types. However, the involvement and effects of miR‑383 on CRC progression and its underlying mechanism remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The above results of miR-383 were in line with previous studies. 15,16 These results unraveled that hsa_circ_0000467 knockdown refrained CRC progression by sponging miR-383-5p.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The above results of miR-383 were in line with previous studies. 15,16 These results unraveled that hsa_circ_0000467 knockdown refrained CRC progression by sponging miR-383-5p.…”
Section: Discussionmentioning
confidence: 82%
“…Also, miR-383 was reported to be dysregulated in CRC and regulate CRC progression. 15,16 Serum/ glucocorticoid regulated kinase 1 (SGK1), located on human chromosome 6q23.2, encodes a serine/threonine protein kinase which plays imperative roles in physiological processes in our body. 17 Recent studies implied that the aberrant expression of SGK1 was also implicated in tumor progression and chemoresistance in various tumors, including CRC.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-383, situated in the seventh intron of the apoptosis-associated tyrosine kinase (AATK) gene, has been identified as a tumor suppressor in several cancers. In colorectal cancer (CRC), miRNA-383 was demonstrated to inhibit tumor growth and metastasis by directly targeting Paired box 6 [36]. An inhibitory effect on cell invasion and metastasis of miR-383 was also illustrated in cervical cancer via suppression of the PI3K-AKT-mTOR signaling pathway by down-regulating PARP2 [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study Yan et al reported that miR-383 inhibited colorectal cancer by directly targeting paired box 6 [18], which is a critical player in eye development [19]. Therefore, AK077216 may regulate paired box 6 through miR-383 to participate in physiological and pathological processes in eye.…”
Section: Discussionmentioning
confidence: 99%